The Effect of Benson Relaxation Technique on Fatigue among Chronic Disease Patients: A Systematic Literature Review - Albianto, Deranito Langlang Paresa; Nurpadilah, Demita; Firmansyah, Deni (Inspirasi Foundation, 2026)
Introduction: Fatigue often afflicts patients with chronic illnesses, adversely affecting their quality of life and limiting their ability to execute daily activities. The Benson relaxation technique, a non-pharmacological method, seeks to reduce weariness by stimulating the body's inherent relaxation response. Evidence suggests that this therapy is a viable, safe, and effective method for mitigating fatigue in those with chronic illnesses Objective: This study aims to assess the efficacy of the Benson relaxation technique in mitigating fatigue among individuals with chronic illnesses. Method: A systematic review was conducted across four databases (PubMed, ProQuest, JSTOR, and Garuda) to identify studies published between 2020 and 2024 examining the application of the Benson relaxation technique among adults aged 18 to 65 with chronic illnesses. Fatigue reduction served as the primary outcome, assessed using validated instruments such as the FSS, MFIS, RPFS, FACIT Fatigue, and CFS. Three independent reviewers performed the search, screening, and quality appraisal following PRISMA guidelines and the CASP Checklist. Result: An analysis of 14 clinical trials with 813 participants demonstrated that the Benson relaxation technique significantly alleviates fatigue in persons suffering from chronic conditions, including coronary heart disease, cancer, multiple sclerosis, and renal failure. The intervention boosts sleep quality, reduces anxiety, and improves general well-being. Enhanced efficacy was noted with extended durations (1–12 weeks) and when conducted bi-daily for 10–60 minutes, particularly when integrated with aromatherapy, music therapy, or deep breathing techniques. Conclusion: The Benson relaxation technique has demonstrated efficacy in alleviating fatigue in persons with chronic illnesses. Consequently, nurses can include this method into non-pharmacological tiredness management strategies to enhance patients' overall quality of life.